Corrigendum to “Comparative analysis of the dynamic behavior of structures equipped with cylindrical and spherical frictional bearings subjected to near-fault earthquakes” [Structures 60 (2024)/105896] (S2352012424000481), (10.1016/j.istruc.2024.105896) - Auad, Gaspar (2024)
No tiene resumen